Social Norms, the Welfare State, and Voting - Assar Lindbeck; Sten Nyberg; Jörgen Weibull (The Research Institute of Industrial Economics (IUI), 1996)
This paper analyzes the interplay between economic incentives and social norms in a public finance context. We assume that to live off one's own work is a social norm, and that the larger the population fraction adhering to this norm, the more intensely it is felt by the individual. It is shown that this may give rise to multiple equilibria and to non-linearities that do not arise from economic incentives alone. In the model, individuals also vote on taxes and transfers. Hence, the social norm influences both their economic and political behavior. We show that monotone and continuous changes in external factors may result in non-monotone, and even discontinuous, changes in the political equilibrium.
Keywords: D60; D63; D69; 330; WELFARE STATE; ETHICS; Soziale Werte; Sozialstaat; Ökonomischer Anreiz; Theorie